1995
DOI: 10.1164/ajrccm.152.4.7551399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of vocal cord dysfunction.

Abstract: Vocal cord dysfunction (VCD) is a respiratory condition characterized by adduction of the vocal cords with resultant airflow limitation at the level of the larynx. Previously, this condition was described in case reports and in small series. This study reviews all patients hospitalized from 1984 through 1991 in whom VCD was diagnosed. Demographic, historical, physiologic, laboratory, and psychiatric factors were statistically analyzed. Ninety-five patients met the criteria for proved VCD; of these, 53 also had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
390
4
41

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(450 citation statements)
references
References 20 publications
15
390
4
41
Order By: Relevance
“…Vocal cord dysfunction -a paradoxical adduction of the vocal cords during inspiration -may mimic asthma [155][156][157]. It may or may not be related to psychological disturbances [158].…”
Section: Dysfunctional Breathing and Vocal Cord Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocal cord dysfunction -a paradoxical adduction of the vocal cords during inspiration -may mimic asthma [155][156][157]. It may or may not be related to psychological disturbances [158].…”
Section: Dysfunctional Breathing and Vocal Cord Dysfunctionmentioning
confidence: 99%
“…It may or may not be related to psychological disturbances [158]. Newman et al reported that 56% of 95 patients with paradoxical vocal cord motion disorder had concomitant asthma [156]. Hussein et al reported vocal cord dysfunction more commonly in women and older individuals, and in association with asthma, GERD and previous abuse [158].…”
Section: Dysfunctional Breathing and Vocal Cord Dysfunctionmentioning
confidence: 99%
“…This abnormality may be identified in people with or without asthma. In a series of such patients, 32% had coexistent asthma, which complicate the diagnosis (17). Some of these patients may be treated with large doses of antiasthma therapy, including oral GCS (18).…”
Section: Exclusion Of Other Diagnosesmentioning
confidence: 99%
“…PVFMD is likely underdiagnosed and this has been shown to lead to increased health care costs [50][51][52]. The prevalence is unknown as there are no large, prospective, population based studies [53].…”
Section: Epidemiologymentioning
confidence: 99%
“…The proposed mechanism is that these higher ventilation bursts require breathing more through the mouth, resulting in cooler and drier air than can irritate the vocal cords [8•]. PVFMD has been found to be present at rates of up to 40 % among patients with refractory or exercise-induced dyspnea [50,[57][58][59]…”
Section: Epidemiologymentioning
confidence: 99%